1990
DOI: 10.1080/02687039008248508
|View full text |Cite
|
Sign up to set email alerts
|

Naming and semantic judgements in dementia of the alzheimer's type

Abstract: Impairment in the ability to name is a robust characteristic of patients with dementia of the Alzheimer's type. However, the cause of this impairment is unclear and explanations range from lexical access problems to disrupted semantic organization. This study investigated demented patients' knowledge of semantic associations and how this knowledge related to naming performance. Ten mildly to moderately demented and five normal patients were tested using a semantic association task and a naming task derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Generally, the dementias are progressive conditions (but see Albert, 1988;Wattis and Church, 1986) in which there is a deterioration in a number of cognitive abilities including learning, memory, attention, language functioning and spatial perception (Bayles, Toemeda and Trosset, 1990;Blennow, Wallin and Gottfries, 1991;Bowles, Obler and Albert, 1987;Flicker, Ferris, Crook and Bartus, 1987;Freed, Corkin, Growdon and Nissen, 1989;Huppert and Tym, 1986;Nebes, 1989;Sommers and Pierce, 1990). Changes in the sufferer's personality may also take place and these may either precede the deterioration in cognitive performance or accompany the later stages (Lishman, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the dementias are progressive conditions (but see Albert, 1988;Wattis and Church, 1986) in which there is a deterioration in a number of cognitive abilities including learning, memory, attention, language functioning and spatial perception (Bayles, Toemeda and Trosset, 1990;Blennow, Wallin and Gottfries, 1991;Bowles, Obler and Albert, 1987;Flicker, Ferris, Crook and Bartus, 1987;Freed, Corkin, Growdon and Nissen, 1989;Huppert and Tym, 1986;Nebes, 1989;Sommers and Pierce, 1990). Changes in the sufferer's personality may also take place and these may either precede the deterioration in cognitive performance or accompany the later stages (Lishman, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty in naming or word retrieval has been observed to be the most obvious early symptom of dementia, regardless of cause, and has been found to occur before other language changes associated with the syndrome are measurable (Bayles, Tomoeda, Kaszniak, & Trosset, 1991;Bayles, Tomoeda, & Trosset, 1990;Chan, Butters, Paulsen, Salmon, Swenson, & Maloney, 1993;Emery & Breslau, 1989;Hodges, Salmon, & Butter, 1992;Huff, Corkin, & Growden, 1986;Shuttleworth & Huber, 1988;Sommers & Pierce, 1990). Naming has been considered a meaningful representation of the integrity of the semantic memory system; naming failures exhibited by individuals with dementia have been examined as a means of identifying the nature of the semantic memory impairment.…”
mentioning
confidence: 96%
“…Studies investigating categorisation skills in adults with dementia have revealed that these individuals show significant deterioration in the structure and/or contents of semantic and conceptual knowledge as compared to their age-matched healthy cohorts (Bayles et al, 1990;Binetti, Magni, Cappa, Padovani, Bianchetti, & Trabucchi, 1995;Chan et al, 1993;Hough, 1998;Hough, May, & Givens, 1992;Sommers & Pierce, 1990). However, the nature and extent of the differences between individuals with dementia and normal elderly adults have not been clear.…”
mentioning
confidence: 97%